Citrulline reduces glyceroneogenesis and induces fatty acid release in visceral adipose tissue from overweight rats. Issue 12 (31st October 2014) - Joffin, Nolwenn; Jaubert, Anne‐Marie; Durant, Sylvie; Bastin, Jean; De Bandt, Jean‐Pascal; Cynober, Luc; Moinard, Christophe; Coumoul, Xavier; Forest, Claude; Noirez, Philippe
<x xml:space="preserve">Abstract</x> Scope High‐fat diet (HFD) increases visceral adipose tissue (AT). Our aim was to evaluate whether citrulline (CIT) affected nonesterified fatty acid (NEFA) metabolism in AT from HFD‐fed rats. Methods and results Rats were fed for 8 weeks with either a control diet (CD) or HFD. Retroperitoneal AT explants were exposed to 2.5 mmol/L CIT for 24 h. We analyzed lipolysis, beta‐oxidation, glyceroneogenesis, and the expression of the key associated enzymes. CIT doubled NEFA release selectively in HFD AT. Phosphorylation of hormone‐sensitive lipase was upregulated 50 and 100% by CIT in CD and HFD AT, respectively. Under CIT, beta‐oxidation increased similarly whatever the diet, whereas glyceroneogenesis, which permits NEFA re‐esterification, was downregulated 50 and 80% in CD and HFD AT, respectively. In the latter, the important decrease in re‐esterification probably explains the rise of NEFA release. A pretreatment with the nitric oxide synthase inhibitor N ω‐nitro‐l‐arginine methyl ester abolished CIT effects. Conclusion These results demonstrate direct lipolytic and antiglyceroneogenic effects of CIT on CD and HFD AT. The selective CIT‐mediated NEFA release from HFD AT was probably the consequence of the drastic decrease in glyceroneogenesis and nitric oxide was a mediator of CIT effects. These results provide evidence for a direct action of CIT on AT to reduce overweight.